2017
DOI: 10.1016/j.fuel.2017.02.057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flue gas components on the adsorption of sulfur oxides on CaO(1 0 0)

Abstract: Due to the prevalence of coal combustion technologies utilizing calcium-based materials, it is important to understand the varied reactions between the flue gas species and these calciumbased materials. Of particular importance is the reaction between sulfur oxides (SO 2 or SO 3) and calcium oxide (CaO), which plays an important role in sulfur retention on fly ash during oxycoal combustion or carbon capture with calcium looping. To better understand these reactions, density functional theory (DFT) calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…The lattice constant of a CaO unit cell with a cubic structure (225 Fm‐3 m space group) was 4.833 Å after geometric optimization. The surface of the CaO (1 0 0), which is the most stable low‐index CaO surface, was selected to study the CO 2 capture characteristic of CaO, as shown in Fig. (a).…”
Section: Resultsmentioning
confidence: 99%
“…The lattice constant of a CaO unit cell with a cubic structure (225 Fm‐3 m space group) was 4.833 Å after geometric optimization. The surface of the CaO (1 0 0), which is the most stable low‐index CaO surface, was selected to study the CO 2 capture characteristic of CaO, as shown in Fig. (a).…”
Section: Resultsmentioning
confidence: 99%
“…When limitations exist in terms of coal property, modification space, or treatment for ABS deposition in air preheaters, SO 3 -specific removal techniques that involve powdered or slurry alkaline sorbents (e.g., those containing calcium, magnesium, or sodium) can be applied (Wolf and Seaba, 2012;Galloway and Padak, 2017;Zheng et al, 2020). This approach can be employed along with existing environmental facilities capable of synergistic SO 3 removal to meet SO 3 emission standard.…”
Section: Analysis Of So3 Control Routesmentioning
confidence: 99%
“…The CaO (1 0 0) surface is used to study the CO2 capture characteristics of CaO, since this surface is the most stable low-index CaO surface, as discussed by Tao et al [40] and Galloway et al [41].…”
Section: Simulation Calculations On the Interactions Between Support mentioning
confidence: 99%